Implementation of the Independent Village Program to Improve the Economy of Muara Madras Village Community, Jangkat Subdistrict, Merangin Regency - Epriadi, Dedi; Jaya, Mulia; Mardansyah, Mardansyah; Fitria, Anggelina Dwi (Universitas Syiah Kuala, 2025)
The Independent Village Program is a local development policy that aims to enhance rural communities' economic resilience through institutional strengthening, local potential utilization, and community empowerment. This study aims to analyze the implementation of the program in Muara Madras Village, Jangkat Subdistrict, Merangin Regency. A qualitative descriptive method was used, with data collected through interviews, observations, and documentation. The findings reveal that the program has had a positive impact on improving community welfare through agriculture, aquaculture, and entrepreneurship training. However, challenges such as weak marketing systems and limited youth involvement remain. The program is considered effective but requires strategic improvements for sustainability.